Embedded RTOS design : insights and implementation - Walls, Colin (Newnes, 2021)
Embedded RTOS Design: Insights and Implementation combines explanations of RTOS concepts with detailed, practical implementation. It gives a detailed description of the implementation of a basic real-time kernel designed to be limited in scope and simple to understand, which could be used for a real design of modest complexity. The kernel features upward-compatibility to a commercial real-time operating system: Nucleus RTOS. Code is provided which can be used without restriction. Gain practical information on: Scheduling, preemption, and interrupts Information flow (queues, semaphores, etc.) and how they work Signaling between tasks (signals, events, etc.) Memory management (Where does each task get its stack from? What happens if the stack overflows?) The CPU context: storage and retrieval after a context switch With this book you will be able to: Utilize a basic real-time kernel to develop your own prototype Design RTOS features Understand the facilities of a commercial RTOS.